The Main Issues of the Application of Legislative Norms in the Field of Insurance in The Republic of Uzbekistan (Eurasian Research Bulletin, 2023)
Under market conditions, it is necessary to form a domestic insurance market that would reflect the entire cash flow, including financial and credit flows. Moreover, the functioning of the insurance market should be based on the use of economic laws, and primarily the law of value, the law of supply and demand. In addition, the successful development of the insurance market is impossible without its regulation, without well-thought-out legislative acts that determine the organization and activities of insurers. Legislation is the basis of the economic order in insurance, and the state, represented by specially authorized bodies, must manage this process by adopting legal norms and supervising their observance. The article deals with topical issues of the formation of the legislation of the Republic of Uzbekistan in the field of insurance, a comparative analysis of the legislation of developed countries is carried out. Practical proposals are given for improving the legislation in this area, the need to adopt a law on compulsory insurance, indicating in it the tasks and obligations of the parties, as well as the powers and procedure for concluding compulsory insurance contracts.